Phase change regulation and enhanced enthalpy in mixed tetrabutylammonium salt hydrates for multi-temperature cold storage applications - Kai Guo; Ziyi Qu; Wenxiang Zhang; Sizhe Zhou; Yonghuan Zang; Xiao Jiang; Zhihan Yang; Qing Xiao; Haojie Gao (Case Studies in Thermal Engineering, 2025)
Semi-clathrate hydrates, with high latent heat, tunability, and excellent stability, show promise as phase change cold storage materials. To meet the varying phase change temperature requirements for different applications, this study investigated the dissociation behavior of hydrates formed from two tetrabutylammonium (TBA+) salt mixtures—FBS (TBAF, TBAB, TBAHSO4) and FCS (TBAF, TBAC, TBAHSO4)—at varying concentrations and ratios using differential scanning calorimetry. The results revealed that tuning the ratios of these mixtures enabled single-peak phase change regulation, ranging from 3.8 °C to 15.1 °C and 26 °C to 28.1 °C. The mixed tetrabutylammonium salt solutions exhibited a synergistic effect, enhancing phase change enthalpy beyond pure solutions, with peak values of 225.77 kJ/kg (FBS 0.7-0.3-0) and 239.48 kJ/kg (FCS 0.5-0.5-0). Further analysis indicated that reducing the molar mass of the mixed anions increased both phase change temperature and enthalpy, with FCS exhibiting a more pronounced improvement. For single-peak phase changes, maximum enthalpies of 225.77 kJ/kg (FBS) and 226.48 kJ/kg (FCS) were observed when the mixed anion molar masses were 25.69 and 20.96 kg/kmol, respectively. These finding highlight the potential of mixed tetrabutylammonium slat hydrates for applications, including high-energy density cold storage, multi-temperature range preservation, and advanced air conditioning systems.